Awareness and perceptions of nutrition support in upper gastrointestinal cancer surgery: A national survey of multidisciplinary clinicians. (December 2021) - Deftereos, Irene; Kiss, Nicole; Brown, Teresa; Carey, Sharon; Carter, Vanessa M.; Usatoff, Val; Ananda, Sumitra; Yeung, Justin MC.
Summary: Background: Patients undergoing surgery for upper gastrointestinal (UGI) cancer are at high risk of malnutrition, and a multidisciplinary approach to management is recommended. This study aimed to determine practices, awareness and perceptions of multi-disciplinary clinicians with regards to malnutrition screening and provision of nutrition support. Methods: A national survey of dietitians, surgeons, oncologists and nurses was conducted using a 30-item online REDCap survey, including questions regarding self-reported malnutrition screening/nutrition support practices, awareness and perceptions, and barriers and enablers. The survey was distributed via professional organisations/networks between 1st September and 30th November 2020. Results are presented as counts and percentages. Results: There were 130 participants (56% dietitians, 25% surgeons, 11% nurses, 8% oncologists). The majority reported that dietitians and nurses performed malnutrition screening, and dietitians and surgeons prescribed nutrition support. Most participants reported that their health service had dietetics support available overall (98%), however only 41% reported having an outpatient service. Participants (>90%) demonstrated very high awareness of the significance of malnutrition and the importance of early nutrition support. Participants mostly perceived dietitians, nurses and surgeons to be responsible for malnutrition screening, whilst responsibility of prescription of nutrition support was mostly dietitians and surgeons. There were a higher number of barriers for the outpatient setting (48%) than the inpatient setting (38%). Conclusions: Participants identified a high awareness of the importance of identification and treatment of malnutrition in UGI cancer surgery. However reported practices varied and appear to be lacking in the outpatient setting, with significant barriers identified to providing optimal nutrition care.